Electromagnetic interference shielding effectiveness of MgO−Al2O3−SiO2 glass-ceramic system - Kumari, P.; Tripathi, P.; Parkash, O.M.; Kumar (Indian Academy of Sciences, 2017)
MgO−Al2O3−SiO2 (MAS)-based glass-ceramic system was prepared using very-low-cost raw materials, i.e., talc, calcined alumina and calcined China clay with titanium dioxide as a nucleating agent. Glass-ceramics were prepared by a two-step process. In the first step, raw materials were mixed in the required proportion and melted at 1450◦C followed by water quench into a glassy frit. In the second step, powdered glass frit was uniaxially dry pressed into pellets followed by sintering at 1200◦C for 3 h. X-ray diffraction pattern of the sintered compact shows well-defined peaks of cordierite along with some anorthite and magnesium titanium oxide. The microstructure study of sample shows the presence of crystalline and glassy phases. Permittivity and permeability measurements were performed in the microwave frequency range 12.4-17 GHz. The permittivity value of 5.7-6.0 and the permeability value of ∼1 were obtained. The reflection and transmission measurements show that the material possesses a shielding effectiveness in the range 2-10 dB over the frequency range 12.4-17 GHz. © Indian Academy of Sciences.
Keywords: Microwave shielding; glass–ceramics; nucleating agent